1998
DOI: 10.1002/(sici)1096-9071(199807)55:3<197::aid-jmv3>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental African HEV infection in cynomolgus macaques (Macaca fascicularis)

Abstract: Experimental infection with hepatitis E virus (HEV) from Africa has not been investigated. Our purpose was to study hepatitis E produced by HEV from Chad (North Africa) and to analyze the genetic sequence of the HEV obtained after animal passage. An HEV-containing fecal sample from Chad was intravenously inoculated in four cynomolgus macaques. When serum Alanine Amino Transferase (ALT) levels rose, open liver biopsy and bile aspiration were performed. In all the monkeys, an ALT rise occurred 25 to 32 days afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 28 publications
3
3
0
Order By: Relevance
“…Specifically, when the vacuolar degeneration and fatty degeneration in hepatocytes is more pronounced, less ORF2 antigen is expressed. The characteristics of the experimental hepatitis E induced by HEV in rhesus monkeys showed similarities in this study, regardless of differences in the HEV genotypes used for infection, and did not differ from those in previous studies [Ticehurst et al, 1992;van Cuyck-Gandre et al, 1998].…”
Section: Discussionsupporting
confidence: 70%
“…Specifically, when the vacuolar degeneration and fatty degeneration in hepatocytes is more pronounced, less ORF2 antigen is expressed. The characteristics of the experimental hepatitis E induced by HEV in rhesus monkeys showed similarities in this study, regardless of differences in the HEV genotypes used for infection, and did not differ from those in previous studies [Ticehurst et al, 1992;van Cuyck-Gandre et al, 1998].…”
Section: Discussionsupporting
confidence: 70%
“…We observed that the first HEV-related event was viral shedding (at 5 to 21 dpi), as has been previously reported [32]. We assume that all of the animals presented with subclinical viral hepatitis independent of the source of the inoculum (swine or human) and the clinical presentation of the original host organism [22,31].…”
Section: Discussionsupporting
confidence: 63%
“…However, the systemic distribution of HEV RNA and antigens is not yet well documented. Moreover, the route of experimental HEV infection in the past has been primarily by intravenous injection, which successfully infects certain animals, such as swine, BALB/c nude mice, and cynomolgus macaques [17][19]. However, the use of an intraperitoneal route for the infection of rabbits with HEV is rarely reported and its efficacy is still unclear.…”
Section: Introductionmentioning
confidence: 99%